Immobilization of DNA Aptamers on Polyester Cloth for Antigen Detection by Dot Blot Immunoenzymatic Assay (Aptablot) - Smiley, Sally; DeRosa, Maria; Blais, Burton (Journal of Nucleic Acids, 2013)
A simple dot blot immunoenzymatic assay system was developed using polyester cloth coated with an oligo-DNA aptamer to provide a high-affinity macroporous surface for the efficient capture of a model protein analyte (thrombin) in complex sample matrices such as foods. Bound thrombin was detected immunoenzymatically using a peroxidase-linked antithrombin antibody and a chromogenic substrate. A unique feature of this approach, which we have termed “aptablot,” is the facile immobilization of DNA aptamers on the polyester surface by cross-linking with a brief exposure to ultraviolet light, and the simple assay format obviating the need for specialized instruments. The assay principle described herein should be broadly applicable to many situations where analytes must be detected in complex samples, with the main limiting factor being the availability of suitable DNA aptamers.